Forecasting of Clean Water Usage by Observing Trend Pattern using Time Series Method - Mahmudi, Mahmudi; Nurillah, Usmau Lidya; Rusdiana, Siti; Saputra, T Murdani (Syiah Kuala University, 2023)
Population growth will increase the need for clean water. One of the clean water providers in the city of Banda Aceh is Local Water Supply Utility (PDAM) Tirta Daroy. To anticipate the surge in demand for clean water, PDAM needs to know the need for clean water in the future. One of the steps that can be taken is to do forecasting with the double exponential smoothing and triple exponential smoothing method. The smallest error value can be found using the mean absolute percentage error (MAPE) formula. Based on research, the double exponential smoothing method provides the most accurate forecast data when the parameter value 0.6 with an error of 3.5%. While the triple exponential smoothing method, the most accurate forecast data is obtained when the alpha value is 0.4 with an error of 3.55%.